Simultaneous Spectrophotometric Estimation of Artesunate and Mefloquine - T. M. Kalyankar; R. B. Kakade; M. S. Attar; A. R. Kamble (Journal of Chemistry)
A simple, rapid, precise, and accurate UV-visible spectrophotometric method has been developed for the simultaneous determination of Artesunate in combination with Mefloquine. For developing the method, methanol was used as a solvent. Artesunate and Mefloquine showed   at  240 nm and 222 nm, respectively. The proposed method was validated as per ICH guideline. The linearity range of Artesunate and Mefloquine were 10–60 and 20–120 μg/mL, respectively. 99.91  ±  0.2740 and 99.56 ± 0.2067  these value represent the percent recovery of Artesunate and Mefloquine respectively The correlation coefficients of Artesunate and Mefloquine were 0.999, and 0.999, respectively. The relative standard deviation for six replicates was always less than 2%. The statistical analysis proves that the method is suitable for the analysis of Artesunate and Mefloquine as the bulk drugs and in pharmaceutical formulation without any interference from the excipients.